Comparison of the Dural Puncture Epidural and Conventional Epidural Analgesia Maintained Using Programmed Epidural Boluses for Labor Analgesia - Mo X; Yu J; Qin Z; Ma J; Chen Y; Chen X (Drug Design, Development and Therapy, 2025)
Xiaofei Mo,* Jie Yu,* Zhimin Qin, Junyi Ma, Yueyue Chen, Xi Chen Department of Anesthesiology, Guangzhou Medical University Affiliated Women and Children’s Medical Center, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xi Chen, Department of Anesthesiology, Guangzhou Medical University Affiliated Women and Children’s Medical Center, Guangzhou Medical University, 9 Jinsui Road, Tianhe District, Guangzhou, 510623, People’s Republic of China, Tel +86 18620688567, Fax +86 020 38076243, Email 877579351@qq.comPurpose: Research indicates that the dural puncture epidural (DPE) technique offers quicker analgesia onset compared to the conventional epidural (EP) technique. Programmed intermittent epidural bolus (PIEB) is superior to continuous epidural infusion (CEI) for maintaining labor analgesia, providing better pain relief and less motor block. Few studies have explored if combining DPE with the PIEB offers additional benefits in analgesia onset, maintenance, local anesthetic consumption, and side effects compared to DPE with EP. We hypothesized that DPE, when combined with PIEB, not only speeds up analgesia onset but also improves neuraxial analgesia maintenance over EP.Patients and Methods: A total of 126 term nulliparous women with singleton pregnancies with a VAS pain score > 50 mm and cervical dilation < 5 cm were randomized to receive EP+PIEB or DPE+PIEB for labor analgesia, initiated with 15 mL of 0.0625% ropivacaine with 0.4 μg/mL of sufentanil using the EP or DPE technique (using 25-gauge Whitacre needle) technique and both maintained with the same solution for PIEB (fixed volume 10 mL, intervals 45 minutes, lockout interval 15 minutes) with labor analgesia. The primary outcome was time to achieving adequate analgesia, defined as a VAS pain score ≤ 30 mm. Secondary outcomes included pain scores, motor blockade, obstetric and neonatal outcomes, and satisfaction with analgesia.Results: Adequate analgesia was achieved faster in the DPE+PIEB group than in the EP+PIEB group (hazard ratio 2.409; 95% CI 1.670 to 3.474, P< 0.001). The median time (interquartile range) to VAS pain score ≤ 30 mm was 10 (7 to 13) minutes for the DPE+PIEB group and 15 (11 to 19) minutes for the EP+PIEB group (P< 0.001). No differences in any of the secondary outcomes between the two groups were observed.Conclusion: DPE with PIEB accelerated onset time but did not improve maintenance of neuraxial labor analgesia over DPE with EP.Keywords: analgesia, epidural, labor pain, spinal puncture